PENGEMBANGAN ANTARMUKA APLIKASI MENGGUNAKAN PRINSIP GENERAL DATA PROTECTION REGULATION - Lokapitasari Belluano, Poetri Lestari; Herman, Herman; Panggabean, Benny Leonard Enrico (Univeristas Muslim Indonesia, 2019)
General Data Protection Regulations (GDRP) regulation which is used to substantiate or individual data protection. the principle of gdpr is transparency where the application users have the right to make changes and access to personal data. so, companies are asked to be transparent about the reasons for collecting the data and the purpose of the data usage. GDPR has purpose to develop personal data protection and user privacy data by managing update data in the form of real-time notification. the method is used for Convention over Configuration paradigm. Prototyping model is used to describe application system workflow using graphics, DBMS management (using PostgreSQL). In Conclusion, prototype web application information system which applies data protection information using the principle of GDRP at user by managing data information updates in the form of real-time notification.